(untitled) (Medical Forum Monthly, 2022)
Objective: This study was undertaken to evaluate the loco regional recurrence cases of OSCC in the twin cities of Pakistan during the period of 2015 to 2018. Study Design: A retrospective, descriptive, cohort study Place and Duration of Study: This study was conducted at the Islamic International Dental College, Islamabad from August 2019 to July 2020. Materials and Methods: A sample size of 40 patients with OSCC was calculated. Data was collected from the clinical and histopathological reports of the OSCC patients. %). Demographic data regarding age, gender along with clinic-pathological variables such as tumor stage, primary tumor site, treatment type, recurrence site, histological grade, tumor resection margins, and lymph node involvement were investigated to deduce the significance of these variables in recurrence. Results: The mean age of the patients was 55.25 and the sample predominantly had females (62.5%). Most common tumor site was found to be the lower alveolar ridge. Out of 40 patients, 8 showed recurrences (20%) with majority on the primary tumor site. Owing to the small sample size, the variables although having a potential of inference did not come out to be statistically significant. Conclusion: Although a high recurrence rate of 20% was seen; however none of the studied variables showed any statistically significant co-relation.